2‐(4‐Ethoxy phenyl)‐4‐phenyl quinoline organic phosphor for solution processed blue organic light‐emitting diodes. (31st May 2018) - Ghate, Minakshi; Kalyani, N. Thejo; Dhoble, S. J.
Abstract: This paper reports the synthesis and characterization of 2‐(4‐ethoxyphenyl)‐4‐phenyl quinoline (OEt‐DPQ) organic phosphor using an acid‐catalyzed Friedlander reaction and the preparation of blended thin films by molecularly doping OEt‐DPQ in poly(methyl methacrylate) (PMMA) at different wt%. The molecular structure of the synthesized phosphor was confirmed by Fourier transform infra‐red (FTIR) spectroscopy and nuclear magnetic resonance spectra (NMR). Surface morphology and percent composition of the elements were assessed by scanning electron microscopy (SEM) and energy dispersive analysis of X‐rays (EDAX). The thermal stability and melting point of OEt‐DPQ and thin films were probed by thermo‐gravimetric analysis (TGA)/differential thermal analysis (DTA) and were found to be 80°C and 113.6°C, respectively. UV–visible optical absorption spectra of OEt‐DPQ in the solid state and blended films produced absorption bands in the range 260–340 nm, while photoluminescence (PL) spectra of OEt‐DPQ in the solid state and blended thin films demonstrated blue emission that was registered at 432 nm when excited at 363–369 nm. However, solvated OEt‐DPQ in chloroform, tetrahydrofuran or dichloromethane showed a blue shift of 31–43 nm. Optical absorption and emission parameters such as molar extinction coefficient (ε), energy gap (Eg ), transmittance (T), reflectance (R), refractive index (n), oscillator energy (E0 ) and oscillator strength (f), quantum yield (φf ), oscillator energy (E0 ), dispersion energy (Ed ), Commission Internationale de l'Éclairage (CIE) co‐ordinates and energy yield fluorescence (EF ) were calculated to assess the phosphor's suitability as a blue emissive material for opto‐electronic applications such as organic light‐emitting diodes (OLEDs), flexible displays and solid‐state lighting technology.